PENERAPAN HUKUM ADAT DALAM MENYELESAIKAN TINDAK PIDANA PENGANIAYAAN ANTAR ATLET PACUAN PADA TRADISI PACU JALUR DI KABUPATEN KUANTAN SINGINGI - Eki Ilhami; Evi Erdianto; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Customary law is the whole positive code of conduct which on the one hand has sanctions and on the other hand it is not codified. In other words, customary law is a custom that has legal consequences. The customary law system is rooted in unwritten regulations that grow and develop and are maintained with the legal awareness of the community. In criminal acts of persecution, especially those that occur between racing athletes in the Kuantan Singini district, are completed according to the Kuantan Singing tradition but the sanctions do not work as set out by the Kuantan Singing custom because of the reasons, as for the objectives of this thesis research, namely: settlement of criminal acts of abuse that occurred between racing athletes according to the customs of Kuantan Singingi Regency. Second, to find out customary sanctions in resolving criminal acts of persecution that occurred between racing athletes in the tradition of racing lanes in Kuantan Singingi Regency.The type of research carried out can be classified into sociological juridical research where the research examines the effectiveness of the law that is currently in effect. This sociological research is a type that is viewed from the purpose of legal research. Sociological or empirical legal research consists of legal identification (unwritten) and research on legal effectiveness. From the results of the study, based on the two problem formulations, it can be concluded. First, the process of resolving the criminal act of persecution in Kuantan Singingi Regency goes through a series of processes where customary justice can be carried out by the customary head, village head or by the management of organizational associations (customary institutions) as previously stated in the peaceful settlement of customary offenses to enforce customary law balance in society. Second, there are two types of traditional sanctions given to racing athletes, the first is individual sanctions and group sanctions. Individual sanctions are given to athletes, namely in the form of being owed in accordance with the agreement and the level of abuse. Group Sanction is a prohibition against racing for a certain time.Keywords: Customary Law, Persecution, Pacu jalur